Transition pathways to 100 % renewable energy in 208 island mini-grids in the Philippines - Michael T. Castro; Laurence L. Delina; Joey D. Ocon (Energy Strategy Reviews, 2024)
Hybrid renewable energy systems have garnered considerable attention as sustainable power sources for remote off-grid islands in the Philippines. Consequently, they have been the subject of numerous techno-economic investigations. However, comprehensive explorations into the viability of 100 % renewable energy (RE) systems for these areas have been limited due to their exorbitant initial outlays. In this work, we modelled the prospective transition of off-grid island mini-grids in the Philippines from the contemporary status quo in 2020 to a fully integrated 100 % RE system by 2050. Our approach involves the gradual shift towards RE adoption instead of the abrupt deployment of RE systems. This maneuver serves a twofold purpose: firstly, it mitigates the adverse economic repercussions stemming from the substantial upfront costs inherent to RE technologies; secondly, it leverages the declining future costs of these technologies. We collected an energy generation and consumption dataset across 208 mini-grids in Philippine off-grid islands. We then simulate the RE transition based on prevailing technology costs at five-year intervals from 2020 to 2050. Afterwards, different scenarios that may affect the energy transition are simulated. Our results indicate that an energy transition steered solely by market dynamics cannot achieve a 100 % RE penetration; hence, we analysed alternative scenarios promoting RE utilization. The immediate discontinuation of all diesel generators by 2050 will lead to a substantial cost uptick at the end of the transition. Integrating biodiesel yields a more measured progression of costs, although this relies upon a nascent market, rendering it susceptible to feedstock supply risks. Recognizing the intermittent nature of RE technologies, we posit that allowing for a certain degree of unmet load fosters greater RE penetration. Nevertheless, this approach compromises the reliability of the system. Our work demonstrates that a 100 % RE transition in Philippine off-grid islands is technically and economically feasible. However, the energy trilemma or the tradeoff between affordability, reliability, and sustainability encumbers the realization of this transition.